A domain-specific approach for assessing physical activity efficacy in adolescents: From scale conception to predictive validity. (January 2016) - Campbell, Nerissa; Gray, Casey; Foley, Louise; Maddison, Ralph; Prapavessis, Harry
Abstract: Objective: To develop and test the utility of a domain-specific physical activity efficacy scale in adolescents for predicting physical activity behaviour. Design: Two independent studies were conducted. Study 1 examined the psychometric properties of a newly constructed Domain-Specific Physical Activity Efficacy Questionnaire (DSPAEQ) and study 2 tested the utility of the scale for predicting leisure- and school-time physical activity. Methods: In study 1, descriptive physical activity data were used to generate scale items. The scales factor structure and internal consistency were tested in a sample of 272 adolescents. A subsequent sample of Canadian ( N  = 104) and New Zealand ( N  = 29) adolescents, was recruited in study 2 to explore the scale's predictive validity using a subjective measure of leisure- and school-time physical activity. Results: A principle axis factor analysis in study 1 revealed a 26-item, five-factor coherent and interpretable solution; representative of leisure and recreation, household, ambulatory, transportation, and school physical activity efficacy constructs, respectively. The five-factor solution explained 81% of the response variance. In study 2 the domain-specific efficacy model explained 16% and 1% of leisure- and school-time physical activity response variance, respectively, with leisure time physical activity efficacy identified as a unique and significant contributor of leisure-time physical activity. Conclusion: Study 1 provides evidence for the tenability of a five factor DSPEAQ, while study 2 shows that the DSPEAQ has utility in predicting domain-specific physical activity. This latter finding underscores the importance of scale correspondence between the behavioural elements (leisure-time physical activity) and cognitive assessment of those elements ( leisure-time physical activity efficacy ). Highlights: A strong emphasis should be placed on the correspondence of efficacy measures with behavioural outcomes in adolescents. The domain specific physical activity efficacy scale (DSPAEQ) assesses efficacy in five independent activity domains. The DSPAEQ improves scale correspondence between physical activity behavioral elements and cognitive assessment of those elements. The DSPAEQ also demonstrates utility for predicting domain-specific physical activity behaviour.